1992
DOI: 10.1007/bf02342512
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain distribution of toluene in rats and in a human autopsy

Abstract: Toluene concentrations in 9 brain regions of acutely exposed rats and that in 11 brain regions of a human case who inhaled toluene prior to death are described. After exposure to toluene by inhalation (2000 or 10,000 ppm) for 0.5 h or by oral dosing (400 mg/kg), rats were killed by decapitation 0.5 and 4 h after onset of inhalation and 2 and 10 h after oral ingestion. After each experimental condition the highest range of brain region/blood toluene concentration ratio (BBCR) was in the brain stem regions (2.85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 14 publications
1
35
0
1
Order By: Relevance
“…While there is no comparable study assessing blood or tissue toluene levels in pregnant rats after repeated binge exposure(s) to high concentrations of inhaled ambient toluene, there are two inhalation studies of perhaps limited relevance in 42-day-old male rats using different patterns of exposure. One study assessed BTLs in Fisher-344 rats during and after exposure accompanying 3 hours of restraint to 99 ppm, 549 ppm, or 1145 ppm of toluene [23] and another assessed BTLs in Wistar rats after a single 30-min inhalation of 2,000 ppm or 10,000 ppm of toluene [2]. Blood or serum toluene levels were assayed in separate rats at different times during the 3-hr exposure [23], or from the same rats (via femoral catheters; [2]), for the next 4 to 10 hours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While there is no comparable study assessing blood or tissue toluene levels in pregnant rats after repeated binge exposure(s) to high concentrations of inhaled ambient toluene, there are two inhalation studies of perhaps limited relevance in 42-day-old male rats using different patterns of exposure. One study assessed BTLs in Fisher-344 rats during and after exposure accompanying 3 hours of restraint to 99 ppm, 549 ppm, or 1145 ppm of toluene [23] and another assessed BTLs in Wistar rats after a single 30-min inhalation of 2,000 ppm or 10,000 ppm of toluene [2]. Blood or serum toluene levels were assayed in separate rats at different times during the 3-hr exposure [23], or from the same rats (via femoral catheters; [2]), for the next 4 to 10 hours.…”
Section: Discussionmentioning
confidence: 99%
“…One study assessed BTLs in Fisher-344 rats during and after exposure accompanying 3 hours of restraint to 99 ppm, 549 ppm, or 1145 ppm of toluene [23] and another assessed BTLs in Wistar rats after a single 30-min inhalation of 2,000 ppm or 10,000 ppm of toluene [2]. Blood or serum toluene levels were assayed in separate rats at different times during the 3-hr exposure [23], or from the same rats (via femoral catheters; [2]), for the next 4 to 10 hours. Gospe and Al-Bayati [23] showed that serum toluene levels asymptoted at ∼15 ppm between 1 hr and 2 hrs into the exposure period, similar to the ∼14.4 ppm level achieved after 2,000 ppm by Ameno, et al [2], and also comparable to the asymptotic levels at 30 min to 45 min in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These have been suspected to be especially toxI~, and therefore dearomatization is widely used, despite the fact that no firm evidence of a distinctive aromatic solvent-related neurotoxicity has emerged from human studies. However, using animal models, both pure aromatics such as xylene and toluene and aromatic mixtures have been implicated as distinctly neur~toxic (LeBel and Schatz 1988;Ameno et al 1992;Mattia et al 1993a,b). These studies have involved relatively high level dosing for rather short times.…”
Section: Introductionmentioning
confidence: 99%